2015
DOI: 10.1007/s00705-015-2489-9
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequence of a novel velarivirus infecting areca palm in China

Abstract: The complete genome of a novel virus, provisionally named areca palm velarivirus 1 (APV1), was identified in areca palm exhibiting leaf yellowing symptoms in Hainan province, China. The genome of APV1 consists of 16,080 nucleotides and possesses 11 open reading frames (ORFs), sharing 56.4% nucleotide sequence identity with little cherry virus 1 (NC_001836.1). The genome organization of APV1 is highly similar to that of members of the genus Velarivirus (family Closteroviridae). Phylogenetic analysis placed APV1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…According to Wang et al (2020), they could not find any phytoplasma in YLD infected plantations from different epidemic areas in Hainan. However, based on RNA-seq (Yu et al, 2015), nextgeneration sequencing, immuno-capture RT-PCR and immunofluorescence assays (Zhang et al, 2021), and RNA-seq and de novo assembly (Cao et al, 2021), it was concluded that APV1 is the causal agent of YLD in Hainan, China. The APV1 belongs to the family Closteroviridae, having a flexuous and filamentous shape observed under transmission electron microscopy (TEM), the typical morphology of species in the family Closteroviridae (Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Wang et al (2020), they could not find any phytoplasma in YLD infected plantations from different epidemic areas in Hainan. However, based on RNA-seq (Yu et al, 2015), nextgeneration sequencing, immuno-capture RT-PCR and immunofluorescence assays (Zhang et al, 2021), and RNA-seq and de novo assembly (Cao et al, 2021), it was concluded that APV1 is the causal agent of YLD in Hainan, China. The APV1 belongs to the family Closteroviridae, having a flexuous and filamentous shape observed under transmission electron microscopy (TEM), the typical morphology of species in the family Closteroviridae (Wang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The APV1 belongs to the family Closteroviridae, having a flexuous and filamentous shape observed under transmission electron microscopy (TEM), the typical morphology of species in the family Closteroviridae (Wang et al, 2020). The genome of APV1-HN associated with YLD from Hainan, China was first sequenced through RNA-seq and was 16,080 nt in length (Yu et al, 2015), while the complete genome sequence of APV1-WYN (Wanning) isolate was approximately 1.5 kb longer than the APV1-HN genome and was recorded to be 17,546 nt in length. In our previously published data regarding APV1 genetic diversity throughout Hainan (China), 20 new complete genomes of APV1 isolates have been identified and sequenced through RNA-seq and de novo assembly and were divided into three phylogroups based on phylogenetic analysis, in which phylogroup A is the most prominent group (>70%), which consists of 16 isolates (Cao et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the production of arecanut is confined to a few states, commercial products are extensively exported across the globe, and approximately 700 million people are dependent on arecanut worldwide [7,8]. Being a perennial crop, arecanut is highly vulnerable to numerous pathogens, including fungi [9][10][11], bacteria [12], phytoplasma [13][14][15], and viruses [16][17][18].…”
Section: Introductionmentioning
confidence: 99%